Iris yellow spot virus (IYSV): nuevo virus en el cultivo de la cebolla en España - Cordoba Selles, C.=700 1 Martinez Priego, L.; Muñoz Gomez, R.M.; Lerma Tobarra, M.L.; Jorda Gutierrez, C.
(En, Es)
ilus., 20 ref.
Keywords: DIAGNOSTICO; THRIPS TABACI; INSECTA; ALLIUM CEPA; INMUNOLOGIA; ESPAÑA